2021
DOI: 10.1002/acr.24202
|View full text |Cite
|
Sign up to set email alerts
|

Modified 2016 American College of Rheumatology Fibromyalgia Criteria, the Analgesic, Anesthetic, and Addiction Clinical Trial Translations Innovations Opportunities and Networks–American Pain Society Pain Taxonomy, and the Prevalence of Fibromyalgia

Abstract: Objective To study the prevalence of fibromyalgia (FM) in the general population according to a 2016 modification of the American College of Rheumatology criteria (FM 2016) and the Analgesic, Anesthetic, and Addiction Clinical Trial Translations Innovations Opportunities and Networks–American Pain Society pain taxonomy criteria (AAPT), and to compare diagnostic and clinical variables between the criteria sets. Methods We studied 2,531 randomly selected subjects from the German general population in 2019. Pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 38 publications
0
17
0
1
Order By: Relevance
“…A study comparing the 2011 and 2016 ACR criteria with the AAPT criteria found considerable agreement between both sets of criteria, although a lower percentage of correct classifications was observed for AAPT criteria than for ACR criteria [ 56 ]. Furthermore, a higher prevalence of FMS in the German general population was obtained with AAPT criteria than with ACR 2016 criteria [ 57 ]. Thus, AAPT criteria seem to diagnose patients with less symptom severity and fewer pain sites [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study comparing the 2011 and 2016 ACR criteria with the AAPT criteria found considerable agreement between both sets of criteria, although a lower percentage of correct classifications was observed for AAPT criteria than for ACR criteria [ 56 ]. Furthermore, a higher prevalence of FMS in the German general population was obtained with AAPT criteria than with ACR 2016 criteria [ 57 ]. Thus, AAPT criteria seem to diagnose patients with less symptom severity and fewer pain sites [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a higher prevalence of FMS in the German general population was obtained with AAPT criteria than with ACR 2016 criteria [ 57 ]. Thus, AAPT criteria seem to diagnose patients with less symptom severity and fewer pain sites [ 57 ]. Further research is required to assess the reliability and validity of the AAPT criteria [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with FM also have functional and emotional disorders, including persistent fatigue, sleep disturbances, paresthesia, cognitive disorders, and mood disturbance [1]. Until 2016, the diagnostic criteria for fibromyalgia included the assessment of pain at 19 sites and a 4-item symptom severity scale from which an overall fibromyalgia severity score, the polysymptomatic distress (PSD) scale, could be calculated [2]. In 2016, a modification added a widespread pain criterion and clarified scoring (2016 criteria) [3].…”
Section: Introductionmentioning
confidence: 99%
“…What we now know for certain is that every set of published fibromyalgia criteria, beginning with Smythe and Moldofsky in 1976 [5], identified a different group of patients [6][7][8][9][10][11]. Even in 2021, two sets of expert research criteria had an unsatisfactory agreement, with one set identifying 73% more individuals with fibromyalgia in a general population study than the other [12]. In addition, general physicians' knowledge about fibromyalgia and the de facto diagnostic agreement with published criteria was and is poor [13][14][15], even in specialty clinics [16].…”
Section: Review I Know It When I See Itmentioning
confidence: 99%